Thermoeconomic Analysis of Csp Air-Steam Mixed Cycles with Low Water Consumption. (August 2015) - Barberis, Stefano; Traverso, Alberto
Abstract: Starting from a state of the art of CSP plants and the undergoing research in hybridization of Gas Turbine plants, the paper investigates alternative plant configurations particularly regarding the integration of CSP technology with mixed cycles because of their low water consumption and the possible use of current CSP components, assessed and compared with a through-life thermo-economic analysis.